2021
DOI: 10.1177/1055665621989508
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Delay in Cleft Surgery at a Tertiary Children’s Hospital in a Major US Metropolitan City

Abstract: Objective: To identify factors associated with late cleft repair at a US tertiary children’s hospital. Design: Retrospective study of children with CL/P using Children’s Hospital Los Angeles (CHLA) records. Setting: US tertiary children’s hospital. Patients/Participants: Patients undergoing primary CL or CP repair at CHLA from 2009 to 2018. Main Outcome Measures: Proportion of children who had delayed primary CL repair or CP repair using CHLA and American Cleft Palate-Craniofacial Association (ACPA) guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…However, variations in speci c percentages can be observed, highlighting the diversity in the anatomical presentation of CLP between different populations. The predominance of isolated cleft lip in our study is consistent with previous studies [12,13,20]. This observation suggests that cleft lips often represent the primary manifestation of the malformation.…”
Section: Resultssupporting
confidence: 93%
“…However, variations in speci c percentages can be observed, highlighting the diversity in the anatomical presentation of CLP between different populations. The predominance of isolated cleft lip in our study is consistent with previous studies [12,13,20]. This observation suggests that cleft lips often represent the primary manifestation of the malformation.…”
Section: Resultssupporting
confidence: 93%
“…Other authors found varying relationships depending on whether it was CL alone, CP alone, or in combination. 32,33 Based on the American Cleft Palate-Craniofacial Association guideline, more than 70% of patients having repair for incomplete CP repair in this study were late compared with 49.2% for patients with incomplete CL. These findings are similar to a 2021 retrospective cohort study in a major US metropolitan city hospital by Stoneburner et al, 33 in which more than 60.0% of children with CP were delayed for repair beyond 18 months of age based on institutional guidelines.…”
Section: Discussionmentioning
confidence: 82%
“…Demographic risk factors for delay of key treatment points have been investigated in the literature. Lower SES (and proxy measurements of such) and non-White race have been shown to be associated with delay of primary lip or palate repair, alveolar bone grafting, and initial referral by a speech specialist 11,12,26–29 …”
Section: Discussionmentioning
confidence: 99%
“…Lower SES (and proxy measurements of such) and non-White race have been shown to be associated with delay of primary lip or palate repair, alveolar bone grafting, and initial referral by a speech specialist. 11,12,[26][27][28][29] Interestingly, almost all of these studies have been conducted in urban US populations or in developing countries, whereas rural populations have seldom been studied. As a result, the above risk factor relationships are not as well established in these populations.…”
Section: Discussionmentioning
confidence: 99%